Molecular Identification of Arbuscular Mycorrhizal Fungal Spores Collected in Korea - Lee, Jaikoo (The Korean Society of Mycology, 2006)
Arbuscular mycorrhizas (AM) have mutualistic symbiosis with plants and thus efforts have been placed on application of these symbiotic relationships to agricultural and environmental fields. In this study, AM fungi were collected from 25 sites growing with 16 host plant species in Korea and cultured with Sorghum bicolor in greenhouse condition. AM fungal spores were extracted and identified using both morphological and molecular methods. Using morphological characters, total 15 morpho-speices were identified. DNA was extracted from single spore of AM fungi and a partial region on 18S rDNA was amplified using nested PCR with AM fungal specific primers AML1/AML2. A total of 36 18S rDNA sequences were analyzed for phylogenetic analysis and 15 groups of AM fungi were identified using both morphological and molecular data of spores. Among the species, 4 species, Archaeospora leptoticha, Scutellospora castanea, S. cerradensis, S. weresubiae were described for the first time in Korea and two species in Glomus and a species in Gigaspora were not identified. Morphological and molecular identification of AM fungal spores in this study would help identify AM fungal community colonizing roots.